Biocontrol Potential of Grapevine Endophytic and Rhizospheric Fungi Against Trunk Pathogens - Silva-Valderrama, Isidora; Toapanta, Diana; Miccono, Maria de los Angeles; Lolas, Mauricio; Díaz, Gonzalo A.; Cantu, Dario; Castro, Alvaro (Frontiers in Microbiology, 2021)
Grapevine Trunk Diseases (GTDs) are a major challenge to the grape industry worldwide. GTDs are responsible for considerable loss of quality, production, and vineyard longevity. Seventy-five percent of Chilean vineyards are estimated to be affected by GTDs. GTDs are complex diseases caused by several fungi species, including members of the Botryosphaeriaceae family and Phaeomoniella chlamydospora, considered some of the most important causal agents for these diseases in Chile. In this study, we isolated 169 endophytic and 209 rhizospheric fungi from grapevines grown under organic and conventional farming in Chile. Multiple isolates of Chaetomium sp., Cladosporium sp., Clonostachys rosea, Epiccocum nigrum, Purpureocillium lilacium and, Trichoderma sp. were evaluated for their potential of biocontrol activity against Diplodia seriata, Neofusicoccum parvum, and Pa. chlamydospora. Tests of antagonism were carried out using two dual-culture-plate methods with multiple media types, including agar containing grapevine wood extract to simulate in planta nutrient conditions. Significant pathogen growth inhibition was observed by all isolates tested. Clonostachys rosea showed 98.2% inhibition of all pathogens in the presence of grapevine wood extract. We observed 100% pathogen growth inhibition when autoclaved lignified grapevine shoots were pre-inoculated with either C. rosea strains or Trichoderma sp.. Overall, these results show that C. rosea strains isolated from grapevines are promising biocontrol agents against GTDs.